Effect of training on the kinematics and performance in overarm throwing in experienced female handball players - van den Tillaar, R.; Marques, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to compare the effect of different training programs upon the kinematics and performance in overarm throwing in experienced female handball players. No significant change in ball velocity (p=0.25) was found after the different training programs. However, the changes that occurred in ball velocity were probably caused by the changes in maximal internal shoulder rotation after the training period as indicated by the positive correlation. However, more studies that examine the kinematics in overarm throwing before and after training have to be conducted before it can be stated with more accuracy that it is maximal internal shoulder rotation velocity, which is responsible for the changes in throwing performance (velocity).